Understanding violence and developing resilience with African American youth in high-poverty, high-crime communities. (April 2019) - McCrea, Katherine Tyson; Richards, Maryse; Quimby, Dakari; Scott, Darrick; Davis, Lauren; Hart, Sotonye; Thomas, Andre; Hopson, Symora
Abstract: The scourge of community violence that besets young citizens in high-poverty U.S. communities of color is a compelling social problem to address. This article synthesizes studies of causes and preventive services for youth violence, including randomized controlled experiments and theoretical, case study contributions. Available evidence indicates that causes of youth violence are complex and interact across multiple layers of social systems. Accordingly, single-factor programs and policies developed for other populations tend to be ineffective for addressing the many injustices with which youth in high-poverty, high-crime communities of color contend. Therefore, we develop a perspective that is developmental, multi-systemic, and restorative of youths' dignity. Responding to researchers' calls for more contextually-grounded case studies of causes and remedies for youth violence, this article focuses on Chicago, where street violence rates in some communities are among the highest in the world and have increased in the last several years. First, we describe the intersectionalities of catalysts of violence, such as institutional racism, police brutality, deficits in child protection, and deep poverty, in a developmental systems-based framework. Next, we frame community service principles with population-specific features, recognizing cultural and community strengths and youths' significant resilience and potential. Drawing from Afrocentric social thought, positive youth development, trauma treatment models, cognitive behavioral, and empowerment approaches, we describe intervention principles for community-based services. Examples are drawn from decades of work with Chicago's impoverished African American youth on the violence-beset south and west sides of Chicago. Highlights: Poverty, racism, maltreatment, trauma, and educational neglect trigger violence Chicago's violence surge followed school, mental health and social service cutbacks Prevention occurs via relationship-focused services and equality-focused policies Programs need tailoring to youths' culture, strengths, supports, and disadvantages Many sources of evidence show effective options to prevent and treat youth violence